Evolution of SARS-CoV-2 antibody repertoire after successive mRNA vaccinations under immunosuppressive treatmentResearch in context - Jim B.D. Keijser; Eileen W. Stalman; Luuk Wieske; Maurice Steenhuis; Koos P.J. van Dam; Laura Y.L. Kummer; Zoé L.E. van Kempen; Joep Killestein; Adriaan G. Volkers; Sander W. Tas; Laura Boekel; Gerrit J. Wolbink; et al. (EBioMedicine)
Summary: Background: Repeated antigen exposure can result in a shifting antibody repertoire. The mechanisms by which this occurs and consequences for cross-variant protection against evolving pathogens remain incompletely understood, particularly in the context of immunosuppressive treatments used in patients with immune-mediated inflammatory diseases (IMID). Methods: To investigate this, we characterised longitudinal changes in the anti-SARS-CoV-2 antibody repertoire over the course of three SARS-CoV-2 mRNA vaccinations in patients with IMIDs treated with methotrexate (MTX) and/or tumour necrosis factor-inhibitors (TNFi), anti-CD20 monoclonal antibodies, no systemic therapy, and healthy controls (total N = 878). We determined serum antibody titres against the receptor-binding domain (RBD) of Wuhan-Hu-1 (WH1) and Omicron BA.1 spike proteins, and assessed ratios thereof between groups as a proxy for cross-reactivity. Findings: We observe emerging anti-BA.1 RBD reactivity over time, notably following a third vaccination. This may be partly explained by affinity maturation, as evaluated by inhibition of ACE2-RBD interactions. Similar trends were seen in patients treated with MTX and/or TNFi, but not in patients on anti-CD20 therapy. SARS-CoV-2 infection prior to vaccination accelerated these effects initially while leading to comparable results after three vaccinations. Interpretation: MTX and TNFi do not qualitatively alter the evolution of the antibody repertoire in response to repeated antigen exposure, whereas anti-CD20 does. These insights may help to optimise vaccination strategies for patients with immune-mediated inflammatory diseases. Funding: This study was supported by ZonMw (The Netherlands Organization for Health Research and Development) and SGF (Collaborating Health Funds).